A Summary Catalogue of the Cyrillic Manuscripts Preservedin Lithuania: Preliminary Materials - Морозова, Надежда (Slavistica Vilnensis, 2017)
The catalogue was prepared in 2008–2011, within the framework of the research project Lithuanica: Literary Heritage of the Ethnoconfessional Minorities of the Grand Duchy of Lithuania, Part II, funded by the Research Council of Lithuania (contract LIT–1–39). The paper provides brief information about all the Cyrillic manuscripts preserved in the libraries and museums of Lithuania. The catalogue is built on the database principle and includes the following fields: 1) title of the manuscript; 2) keeping place; 3) signature; 4) dating; 5) size; 6) storage; 7) provenance. The database contains information about 426 Cyrillic manuscripts: 419 of the manuscripts are kept in Vilnius, 6 books are found in the Biržai Region Museum Sėla and 1 — in the Rokiškis Region Museum. The collected data about the Cyrillic manuscripts preserved in the libraries and museums of Lithuania suggest that Lithuania has the biggest collection of these artifacts among the Baltic States.